Helium flux effects on bubble growth and surface morphology in plasma-facing tungsten from large-scale molecular dynamics simulations. (17th May 2019) - Hammond, Karl D.; Naeger, Ian V.; Widanagamaachchi, Wathsala; Lo, Li-Ta; Maroudas, Dimitrios; Wirth, Brian D.
Abstract: We investigate helium flux effects on helium transport and surface evolution in plasma-facing tungsten using molecular dynamics. The simulations span two orders of magnitude, from ITER-relevant levels to those more typical of simulations published to date. Simulation times of up to 2.5 µs (corresponding to actual fluences of m −2 ) are achieved, revealing concerted bubble-bursting events that are responsible for significant and very sudden changes in surface morphology. The depth distribution of helium depends very strongly on helium flux: helium self-trapping becomes more probable near the surface at high flux, and a layer of near-surface bubbles forms. Helium retention prior to the onset of bubble bursting is also substantially lower at low flux than it is at high flux. Surface features at low fluence are correlated with the positions of bubbles, but at high fluence, bubbles tend to coalesce, venting to the surface at one or more locations and leaving large interconnected cavities below the surface. Ruptured bubbles may serve as pathways deeper into the material, allowing helium to bypass the layer of near-surface bubbles and fill deeper, potentially much larger, bubbles that can produce more substantial surface features. Deeper bubbles also emit prismatic dislocation loops that can fill in cavities closer to the surface. Our results suggest that nearly all molecular dynamics simulations published to date are hampered by finite-size effects, and that helium flux is a very important parameter in determining the behavior of helium in plasma-facing components.